Mitophagy Failure in Fibroblasts and iPSC-Derived Neurons of Alzheimer’s Disease-Associated Presenilin 1 Mutation - Martín-Maestro, Patricia; Gargini, Ricardo; A. Sproul, Andrew; García, Esther; Antón, Luis C.; Noggle, Scott; Arancio, Ottavio; Avila, Jesús; García-Escudero, Vega (Frontiers in Molecular Neuroscience, 2017)
Familial Alzheimer’s disease is clearly related with the accumulation of amyloid-beta and its deleterious effect on mitochondrial function is well established. Anomalies in autophagy have also been described in these patients. In the present work, functional analyses have been performed to study mitochondrial recycling process in patient-derived fibroblasts and neurons from induced pluripotent stem cells harboring the presenilin 1 mutation A246E. Mitophagy impairment was observed due to a diminished autophagy degradation phase associated with lysosomal anomalies, thus causing the accumulation of dysfunctional mitochondria labeled by PARK2. The failure of mitochondrial recycling by autophagy was enhanced in the patient-derived neuronal model. Our previous studies have demonstrated similar mitophagy impairment in sporadic Alzheimer’s disease; therefore, our data indicate that mitophagy deficiency should be considered a common nexus between familial and sporadic cases of the disease.